2022
DOI: 10.3390/vetsci9010020
|View full text |Cite
|
Sign up to set email alerts
|

The Performance and Carcass Characteristics of Black Baladi Kids Fed Diets with Graded Quantities of Sweet Lupin Grain (Lupinus angustifolius)

Abstract: A study was conducted to examine how lupin grains (LUPs) feeding affected nutritional intake, digestibility, growth, and carcass characteristics in kids. A total of 24 growing black kids (initial body weight (BW) = 16.4 ± 0.49 kg) were allocated to one of three diets at random. Lupin was included in the diet at a rate of 0 (control; CON), 100 (LUP100), or 200 g/kg (LUP200) of total dry matter (DM). The trial lasted for 91 days divided into 7 and 84 days to be used for adaptation and data collection, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…As conventional imported feed ingredients may negate profit margins for sheep, livestock producers have begun to search for alternative feeds at lower costs [3]. This research program conducted a series of experiments and found that the use of alternative feeds decreases the cost of production without impacting the health status of small ruminants [2][3][4][5][6]. Feeding by-products from local sources, such as pomegranate seed pulp (PSP) and coconut meal (COC), to livestock can reduce the cost of milk production and increase profits.…”
Section: Introductionmentioning
confidence: 99%
“…As conventional imported feed ingredients may negate profit margins for sheep, livestock producers have begun to search for alternative feeds at lower costs [3]. This research program conducted a series of experiments and found that the use of alternative feeds decreases the cost of production without impacting the health status of small ruminants [2][3][4][5][6]. Feeding by-products from local sources, such as pomegranate seed pulp (PSP) and coconut meal (COC), to livestock can reduce the cost of milk production and increase profits.…”
Section: Introductionmentioning
confidence: 99%